Establishment of a non‐alcoholic fatty liver disease model by high fat diet in adult zebrafish - Xiang Li; Lei Zhou; Yuying Zheng; Taiping He; Honghui Guo; Jiangbin Li; Jingjing Zhang (Animal Models and Experimental Medicine)
Abstract Background Non‐alcoholic fatty liver disease (NAFLD) has become the most common chronic liver disease in recent years, but the pathogenesis is not fully understood. Therefore, it is important to establish an effective animal model for studying NAFLD. Methods Adult zebrafish were fed a normal diet or a high‐fat diet combined with egg yolk powder for 30 days. Body mass index (BMI) was measured to determine overall obesity. Serum lipids were measured using triglyceride (TG) and total cholesterol (TC) kits. Liver lipid deposition was detected by Oil Red O staining. Liver injury was assessed by measuring glutathione aminotransferase (AST) and glutamic acid aminotransferase (ALT) levels. Reactive oxygen species (ROS) and malondialdehyde (MDA) were used to evaluate oxidative damage. The level of inflammation was assessed by qRT‐PCR for pro‐inflammatory factors. H&E staining was used for pathological histology. Caspase‐3 immunofluorescence measured apoptosis. Physiological disruption was assessed via RNA‐seq analysis of genes at the transcriptional level and validated by qRT‐PCR. Results The high‐fat diet led to significant obesity in zebrafish, with elevated BMI, hepatic TC, and TG. Severe lipid deposition in the liver was observed by ORO and H&E staining, accompanied by massive steatosis and ballooning. Serum AST and ALT levels were elevated, and significant liver damage was observed. The antioxidant system in the body was severely imbalanced. Hepatocytes showed massive apoptosis. RNA‐seq results indicated that several physiological processes, including endoplasmic reticulum stress, and glucolipid metabolism, were disrupted. Conclusion Additional feeding of egg yolk powder to adult zebrafish for 30 consecutive days can mimic the pathology of human nonalcoholic fatty liver disease.